Effects of Organizational Culture, Communication, Work Environment and Motivation on Organizational Commitment in Improving Employee Performance at the Aceh Besar District Attorney's Office - Febyolla Presilawati; Erlinda Erlinda; Haru Firdaus (Universitas Bina Sarana Informatika, 2026)
Companies and organizations are currently facing challenges to improve employee performance in an increasingly competitive business environment. One of the factors that can affect employee performance is organizational commitment, which is influenced by organizational culture, communication, work environment, and employee motivation. This study aims to analyze the effect of organizational culture, communication, work environment, and motivation on employee performance at the Aceh Besar District Attorney's Office. The research method used is a quantitative approach with Structural Equation Modeling (SEM) analysis. The research sample consisted of 68 employees of the Aceh Besar District Attorney's Office selected by proportional random sampling method. Data were collected through questionnaires measuring variables of organizational culture, communication, work environment, motivation, organizational commitment, and employee performance. The results showed that organizational culture and employee motivation have an indirect effect on performance through organizational commitment. Meanwhile, organizational communication and work environment did not show a significant influence on employee performance. Organizational commitment is proven to have a positive and significant influence on employee performance. In conclusion, to improve employee performance, the Aceh Besar District Attorney's Office needs to strengthen a positive organizational culture, increase employee motivation, and build stronger organizational commitment. Thus, the organization can achieve its goals more effectively and efficiently.